Caseworkers' perspective on risk factors in the family environment influencing mothers' difficulties in meeting children's needs. (November 2017) - Bérubé, Annie; Lafantaisie, Vicky; Clément, Marie-Ève; Coutu, Sylvain; Dubeau, Diane; Caron, Josée; Lacharité, Carl
Abstract: Objectives: This study examines, from the caseworkers' point of view, which needs of children are the most difficult for parents in neglectful contexts to respond to and which risk factors make this response more difficult. Method: A sample of 55 parents being followed by child protection services for neglect or high risk of neglect accepted to participate in the study. Their caseworker filled out a grid regarding the response provided to the children's needs and the risk factors in the family environment. Results: The results indicate that the children's age is related to the difficulties of responding to their needs. The caseworkers are particularly concerned about guidance and boundaries provided to preschool-age children, but less so about that provided to school-age children. When the children's age is controlled for, parents' mental health problems explains a significant proportion of the variance in parents' response to their children's need for stimulation, emotional warmth, and guidance and boundaries. Caseworkers' worries about drug and alcohol misuse also explain a significant proportion of their concerns about the mothers' ability to ensure their child's safety. Conclusion: Caseworkers are more worried about the parental response offered to preschool children than to school-age ones. However, a constant and coherent response to growing children is still important for their developmental trajectories. Moreover, mental health and substance abuse explain caseworkers' concerns about mothers' engagement toward their child. These data raise questions about which type of services to offer, because intervening in families where parents deal with personal issues while addressing child neglect is complex. Highlights: Many factors can influence caseworkers' perception about how children's needs are met in context of child neglect. Caseworkers are more worried about the guidance and boundaries offered to preschool children than to school-age ones. Mental health problem in mothers increases concerns about child stimulation, emotional warmth, and guidance and boundaries. Substance abuse is associated with worries among caseworkers about the mothers' capacity to ensure their child's safety. Our results raise questions about how to address the divergent realities of families living in the context of child neglect.